Comparative efficacy of gas therapy for diabetic foot ulcers using network meta-analysis - Jing Yang; Peng Ning; Jiali Huang; Hong Ouyang; Jiaxing Zhang; Fan Yang; Hongyi Cao; Fan Zhang (PeerJ)
Objective Diabetic foot ulcers (DFUs) pose significant clinical challenges, with gas therapy emerging as a promising intervention. However, the comparative efficacy of various gas therapy modalities remains unclear. This study evaluates the effectiveness of different gas therapies, particularly hyperbaric oxygen therapy (HBOT), in improving DFU outcomes. Methods We searched three major databases, PubMed, Embase, and the Cochrane Library, for randomized controlled trials (RCTs) published up to March 3, 2024, assessing the efficacy of different gas therapies in managing DFUs. Primary outcomes included ulcer healing and area reduction rates, while secondary outcomes encompassed healing time, amputation rate, and adverse events. A network meta-analysis was performed using R, with surface under the cumulative ranking curve (SUCRA) values calculated to rank therapies. Results A total of 34 RCTs involving 2,268 DFUs were included in this analysis. HBOT ranked highest for the healing rate (SUCRA = 0.8 14) and area reduction rate (SUCRA = 0.730) but also had a higher amputation rate (SUCRA = 0.621). Except for carbon dioxide therapy, HBOT demonstrated significantly greater healing rates than standard of care (SOC) (mean difference (MD) = −2.71, 95% confidence interval (CI) [−4.85 to −1.34]) and topical oxygen therapy (MD = −2.03, 95% CI [−4.50 to −0.32]), while pairwise comparisons among other gaseous therapies were non-significant (P > 0.05). For wound area reduction, HBOT was superior to SOC (MD = 0.39, 95% CI [0.11–0.67]), whereas differences among other gaseous therapies remained non-significant (P > 0.05). There was substantial heterogeneity in the area reduction rate in net work analysis (I2 = 87%). Subgroup analyses revealed greater area reduction in DFUs treated with HBOT when the treatment duration exceeded six weeks. Conclusions HBOT improves ulcer healing and area reduction rates in DFU patients; however, its association with higher amputation rates warrants cautious use, considering resource availability. Given the limited number and quality of included studies, further high-quality research is needed to validate these findings.